Effects of dietary lysine levels on growth performance and antioxidative capacity in channel catfish Ictalurus punctatus. (22nd June 2022) - Yu, Hailuo; Yang, Mengxi; Xiao, Tiaoyi; Luo, Yiwen; Ren, Wei; Ye, Lihai; Zhang, Yanling; Dong, Xiaohu; Li, Yaoguo
Abstract: A feeding trial was performed to investigate the effects of dietary lysine levels on growth performance and antioxidative capacity of channel catfish Ictalurus punctatus . Five isonitrogenous and isoenergetic diets with 19.3 (the control), 20.5, 22.1, 23.1 and 24.4 g kg −1 of lysine were formulated. Results showed that compared with the control, 23.1 g kg −1 dietary lysine increased the weight gain rate (WGR) and specific growth rate (SGR), and decreased the feed conversion ratio (FCR; p  < 0.05). Based on the quadratic regression analysis of SGR and FCR, the optimal dietary lysine level was 22.2 and 21.9 g kg −1, respectively. As dietary lysine levels increasing from 19.3 to 24.4 g kg −1, the catalase activity increased significantly, while the malondialdehyde content decreased ( p  < 0.05). The mRNA levels of antioxidative genes in liver were markedly upregulated with the increase of lysine levels ( p  < 0.05). Meanwhile, the mRNA levels of target of rapamycin (TOR), kelch‐like ECH‐associated protein 1 (Keap1) and nuclear factor erythroid 2‐related factor 2 (Nrf2) were increased ( p  < 0.05). In conclusion, 22.2 and 21.9 g kg −1 dietary lysine could improve the growth performance of channel catfish. Besides, 24.4 g kg −1 dietary lysine enhanced antioxidative capacity via the TOR/Keap1/Nrf2 signalling pathway.